Novel and diverse mycoviruses co-infecting a single strain of the phytopathogenic fungus Alternaria dianthicola - Zhong, Jie; Li, Ping; Gao, Bi Da; Zhong, Shuang Yu; Li, Xiao Gang; Hu, Zhao; Zhu, Jun Zi (Frontiers in Cellular and Infection Microbiology, 2022)
Alternaria dianthicola is a pathogenic fungus that causes serious leaf or flower blight on some medicinal plants worldwide. In this study, multiple dsRNA bands in the range of 1.2-10 kbp were found in a Alternaria dianthus strain HNSZ-1, and eleven full-length cDNA sequences of these dsRNA were obtained by high-throughput sequencing, RT-PCR detection and conventional Sanger sequencing. Homology search and phylogenetic analyses indicated that the strain HNSZ-1 was infected by at least nine mycoviruses. Among the nine, five viruses were confirmed to represent novel viruses in the families Hypoviridae, Totiviridae, Mymonaviridae and a provisional family Ambiguiviridae. Virus elimination and horizontal transmission indicated that the (-) ssRNA virus, AdNSRV1, might be associated with the slow growth and irregular colony phenotype of the host fungus. As far as we know, this is the first report for virome characterization of A. dianthus, which might provide important insights for screening of mycovirus for biological control and for studying of the interactions between viruses or viruses and their host.